Deep eutectic solvents: designer fluids for chemical processes. Issue 4 (12th December 2017) - Wazeer, Irfan; Hayyan, Maan; Hadj‐Kali, Mohamed K
Abstract: The increasing demand for multi‐task green solvents has spurred the development of next‐generation liquid media such as deep eutectic solvents (DESs), which have recently attracted increased attention. DESs are mixtures of salts and complexing agents, having freezing points lower than those of starting individual components. Similarly to ionic liquids, DESs exhibit distinctive properties such as chemical and thermal stability, biodegradability, non‐flammability, and cost effectiveness. These features account for their wide range of applications, e.g. as extractants, reactants, catalysts, reaction media, additives, and lubricants. This review summarizes the recent research efforts directed at exploring the potential applications of DESs in various chemical processes. With the rapid publication of reports on this new generation of solvents, other roles also are expected to be seen sooner or later. © 2017 Society of Chemical Industry